The Effect of Minimum Wage, Unemployment, and Zakat, Infaq, Sadaqah on Poverty in West Java in the 2015-2021 Period - Shofiyyah Az zahra; Ajeng Kartika Galuh (Islamic Economics and finance in Focus, 2025)
Covid-19 has made poverty in Indonesia increase again. The main source of household income wages, has decreased and unemployment has increased. The minimum wage policy was established to increase workers’ per capita wages. While economic growth has decreased, Zakat, Infaq, Sadaqah (ZIS) funds have consistently increased. Income distribution according to conventional and Islamic economics has an important role in reducing poverty. Researchers see that the variables of minimum wages, unemployment, and ZIS in previous studies still have inconsistent results and previous studies have not combined the three variables together. So, this study aims to determine the effect of minimum wage, unemployment, and ZIS on poverty in West Java. This study uses a quantitative approach with multiple linear regression analysis. The results prove that minimum wage and unemployment have a significant effect on poverty, while ZIS has no significant effect on poverty.